Rosmini: a philosopher in search of the economy - Hoevel, Carlos (2014)
Fil: Hoevel, Carlos. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Instituto de Investigación Francisco Valsecchi; Argentina